Coccolithophore variability across Marine Isotope Stage 11 in the Pacific sector of the Southern Ocean and its potential impact on the carbon cycle. (19th August 2017) - Saavedra‐Pellitero, Mariem; Baumann, Karl‐Heinz; Lamy, Frank; Köhler, Peter
Abstract: Proxy‐based reconstructions of past changes in the marine biological carbon pumps are limited, especially in the Southern Ocean. This work provides new insights into the productivity variations in the Pacific sector of the Southern Ocean. We present new data derived from three sediment cores that show glacial/interglacial coccolithophore variability across Marine Isotope Stage 11 (MIS 11). The cores were retrieved during R/V Polarstern cruise PS75 from the Subantarctic Zone and Polar Front Zone at the western flank of the East Pacific Rise and in the vicinity of the Antarctic‐Pacific Ridge. Coccolithophore assemblages were overwhelmingly dominated by the species Gephyrocapsa caribbeanica and small Gephyrocapsa . Total numbers of coccoliths, coccolith accumulation rates, coccolith fraction (CF; <20 μm fraction) Sr/Ca data, and temperature‐corrected CF Sr/Ca records consistently showed an increase in coccolithophore productivity during Termination V (MIS 12‐11 boundary), highest productivity throughout MIS 11 (~424–374 kyr), and a decrease during late MIS 11 in all the cores. We end with a discussion of back‐calculated coccolith calcification rate in the surface ocean and its potential contribution to changes in the concentration of atmospheric CO2 . Key Points: High coccolithophore carbonate accumulation rates occurred across MIS 11 in the Pacific sector of the Southern Ocean Coccolithophore assemblages were by far dominated by gephyrocapsids, mostly the heavily calcified Gephyrocapsa caribbeanica A potential contribution of the increased coccolithophore calcification to a rise in atmospheric CO2 across Termination V is suggested